Post-race reactions: The emotional paradox of high performance and anxiety - a conventional content analysis - Sofia Ryman Augustsson; Malin Bergh; Kornelia Petersson (BMC, 2024)
Abstract Background Studies examining post-race emotional experiences in the context of endurance races among recreational athletes are scarce. The purpose of this study was to describe how recreational athletes experience the time after completing an endurance race. Methods In this study, a qualitative study design was used, and data collection was carried out with semi-structured interviews. The selection of subjects was completed systematically through criterion selection. The selection criteria were men and women, aged 18 years or older, who had completed an endurance race, and finished, lasting at least 180 min within the past 12 months. The interviews were analyzed using conventional qualitative content analysis. Results Sixteen recreational endurance athletes who, within six months, had completed an endurance race of running, cycling, cross-country skiing or Ironman, participated and were interviewed. Four overarching themes emerged from the analysis: "High on life", "Loss of energy, Ambivalence and Melancholy", "Activity-charged emotions", and "Dimensions of emotions over time and new goals", describing the content of the interviews. Conclusions Endurance athletes experienced varied post-race emotions that were both physically and mentally challenging, suggesting a holistic approach to managing post-race emotions would be beneficial. From the athletes' perspectives, post-race feelings were dependent on many factors, including time spent training for a specific race, and perceived inability to set new goals for an upcoming training period. Setting future goals prior to an event may be a tool for reducing the risk of negative post-race emotions, including post-race blues.